Quill mites of the family Syringophilidae (Acariformes: Prostigmata) associated with Cockatoos (Psittaciformes: Cacatuidae) - Marciniak, Natalia; Skoracki, Maciej; Hromada, Martin (Zootaxa, 2019)
Quill mites of the family Syringophilidae (Acariformes: Prostigmata: Cheyletoidea) parasitizing cockatoos (Psittaciformes: Cacatuidae) are reviewed. Three new species are described: Neoaulobia cacatui sp. nov. from the Yellow-tailed Black-Cockatoo Calyptorhynchus funereus (type host) in Australia and the Palm Cockatoo Probosciger aterrimus in Papua New Guinea, Lawrencipicobia calyptorhyncha sp. nov. from the Glossy Black-cockatoo Calyptorhynchus lathami in Australia, and Lawrencipicobia sulphurea sp. nov. from the Yellow-crested cockatoo Cacatua sulphurea in Indonesia (West Timor).